Evaluation and characterization of charcoal briquettes using damar binder for sustainable energy - Nurdin, Hendri; Waskito, Waskito; Harmanto, Dani; Purwantono, Purwantono; Kurniawan, Andre; Yuvenda, Dori; Anaperta, Yoszi Mingsih (Teknomekanik, 2025)
Palm kernel shells have great potential as biomass and renewable energy sources. Its utilization has not been maximized which is only directly burned which causes air pollution. The accumulation of solid waste in the crude palm oil processing industry negatively impacts the environment. The research aims to determine the characteristics and quality of charcoal briquettes with palm kernel shell carbonization. The main findings of this study are the calorific value, water content, volatile matter, ash content, and fixed carbon in palm kernel shell charcoal briquettes with damar binder. The experimental research method was carried out by carbonizing the raw materials of palm kernel shell briquettes, applying various concentrations of damar binder mixtures. The technical parameters of briquette making were 10 MPa pressure, 60 mesh size, and different carbonization temperatures by furnace. The calorific and proximate were empirically measured by using a bomb calorimeter. This research produced palm kernel shell charcoal briquettes with a calorific value of 30.72 MJ/kg at a carbonization temperature of 500oC and concentration of 85%:15%, a moisture content of 5.18%, volatile matter of 32.72%, ash content of 2.81%, and fixed carbon of 57.90%. Palm kernel shell charcoal briquetting technology is potentially a recommended alternative solid fuel. Consequently, developing renewable energy that is environmentally friendly leads to achieve sustainable energy security. By utilizing waste, the negative impacts on the environment can be overcome and energy needs are also resolved.